(untitled) (Al-Mansour Journal, 2023)
Software development seems to be on the rise, owing to growing necessity for businesses to go online. There is a push to develop upgraded applications that will help businesses become more efficient and grow. Today’s software architectures include monolithic and microservices, which are both popular and powerful. For microservice architecture brings practical benefits such like scalability and flexibility, as well as being a cost-effective means of developing large applications. On the flipside, the monolithic approach is losing favor since it endangers current software delivery methodologies. In this paper, we will discuss the differences between Microservices and Monolithic Architectures, highlighting their strengths and weaknesses in each, and minding a comparative depending on selecting a simple travel application structure, which wins to be chosen as the best choice in software business world.